Concomitant tumor resistance: The role of tyrosine isomers in the mechanisms of metastases control - Ruggiero, Raul Alejandro (2012)
Concomitant tumor resistance (CR) is a phenomenon in which a tumor-bearing host is resistant to the growth of secondary tumor implants and metastasis. Although previous studies indicated that T-cell-dependent processes mediate CR in hosts bearing immunogenic small tumors, manifestations of CR induced by immunogenic and nonimmunogenic large tumors have been associated with an elusive serum factor. In a recently published study, we identified this factor as meta-tyrosine and ortho-tyrosine, 2 isomers of tyrosine that would not be present in normal proteins. In 3 different murine models of cancer that generate CR, both meta- and orthotyrosine inhibited tumor growth. Additionally, we showed that both isoforms of tyrosine blocked metastasis in a fourth model that does not generate CR but is sensitive to CR induced by other tumors. Mechanistic studies showed that the antitumor effects of the tyrosine isomers were mediated in part by early inhibition of the MAP/ERK pathway and inactivation of STAT3, potentially driving tumor cells into a state of dormancy in G 0-phase. Other mechanisms, putatively involving the activation of an intra-S-phase checkpoint, would also inhibit tumor proliferation by accumulating cells in S-phase. By revealing a molecular basis for the classical phenomenon of CR, our findings may stimulate new generalized approaches to limit the development of metastases that arise after resection of primary tumors or after other stressors that may promote the escape of metastases from dormancy, an issue that is of pivotal importance to oncologists and their patients. ©2012 AACR.